Economic performance of India amidst high CO2 emissions - Udemba, Edmund Ntom; Gungor, Hasan; Bekun, Festus Victor; Kirikkaleli, Dervis (Elsevier, 2021)
In recent times, the Indian economy has enjoyed a positive economic trajectory. However, the economy remains vulnerable to domestic and geographical risk as it relates to environmental degradation. The Indian economy is reputed as one of the leading emitters of carbon dioxide (CO2) emissionsglobally.. In the literature, there is no consensus on the contradiction between decoupling economic growth from CO2 emission in India and other regions of the globe. By drawing on the Sustainable Development Goals (SDGs) agenda and its 2030 targets, this study examines the relationship between responsible energy consumption (SDGs 7, 12), climate issues (SDGs 13), and economic growth (SDGs 8) for the case of India. Thus, the present study seeks to investigate the implications of CO2 emissions on Indian economic growth (GDP) with a focus on the energy intensity in the country's economy. To explore the nexus between economic growth and environmental degradation in a carbon income function, openness to trade and energy use were added as additional variables to circumvent the problem of omitted variable bias. Autoregressive Distributed Lag (ARDL) with the modified Wald test of Toda Yamamoto (T-Y) were applied to annual time series data from 1975-2017. The study reveals a long-term equilibrium association among the described variables over the considered period. Furthermore, a statistically significant negative relationship is observed between CO2 emissionsand trade openness and economic growth. This study validates the energy-induced economic growth as reported by the ARDL regression. This is also corroborated by the causality analysis results, as a uni-directional relationship was observed running from energy utilization to income (GDP). Thus, the Indian government officials should not adopt conservative energy policies, as this will be detrimental for economic growth given that the economy is dependent on energy. However, based on the growing environmental consciousness around the world, there is a need to shift the energy mix in India to renewables to make uses of cleaner energy sources and create environmentally friendly ecosystems. (C) 2020 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: CO2 emissions; Energy use; Openness; Economic growth; sustainable development; India